A Bias for Action - Bruch, Heike; Ghoshal, Sumantra (Ascent Audio, 2020)
In A Bias for Action, Sumantra Ghoshal and Heike Bruch reveal that only ten percent of managers act purposefully to get truly important work done. A Bias for Action shows that great managers produce results not by motivating others, but by engaging their own willpower through a powerful combination of energy and focus. Bruch and Ghoshal provide simple strategies for bolstering individual willpower and action-taking abilities, and explore ways to marshal the willpower of others to encourage collective action.